MACRO ECONOMIC REVIEW OF JA KARTA ISLAMIC INDEX STOCK RETURNS - Windari; Dede Ruslan; M. Fitri Rahmadana (CV. Radja Publika, 2024)
This study tries to examine the problem of whether there is macroeconomic influence (inflation, Indonesian interest rates) on JII stock returns on the IDX. The data used in this study is secondary data using combined time series data (time period) with Cross Section data (8 selected companies) based on the annual financial statements of shares that are incorporated in the JII from 2018-2023. The results of both simultaneous and partial data processing show that Macroeconomics (inflation and Indonesian interest rates) affect stock returns with a significance level below 0.05. Stocks of companies classified in the Jakarta Islamic Index are those whose types, products, services provided, contracts, and management methods do not contradict Sharia principles. Similarly, regarding profit-sharing, it must also comply with Sharia principles, devoid of interest elements, as interest falls under usury, and activities involving usury are prohibited in the Sharia capital market in accordance with the fatwa decision of the National Sharia Council No: 40/DSN-MUI/X/2003.